Barriers to BIM Adoption in Brazil - Arrotéia, Aline V.; Freitas, Raissa C.; Melhado, Silvio B. (Frontiers in Built Environment, 2021)
Purpose: The research goal was to investigate the main barriers faced by a large Brazilian construction company in their efforts to thoroughly implement BIM. This study focused on the analysis of understanding the barriers to BIM adoption and the usage of 3D/4D dimensions on the development of an infrastructure project. Research methodology: The research methodology was exploratory and qualitative carried out through a single case study approach made upon bibliographical research, company document analysis, project document analysis, interviews, informal conversations, and observations. The research methodology was developed in six months (from June to December 2019) divided in three main phases: Phase 1: definition and design, Phase 2: preparation and collection, and Phase 3: data analysis and conclusion. Data collection was developed using a semi structured research protocol with two different semi structured questionnaires: The first questionnaire aimed at collecting data regarding to BIM implementation in the company’s organizational context. The second one focused on the understanding of BIM adoption in the project and on the investigation of the main barriers related to the usage of 3D and 4D modeling in the project studied. Findings: Regarding to BIM implementation in the company, despite the company studied is a construction company in the infrastructure sector, BIM was considered more efficiently in the design phase and flawed in the construction phase. Findings shown that BIM has improved the information management of the design itself and its interface with construction phase. In relation to the usage of BIM in the project, it was noticed a more collaborative work environment due to the effectiveness of communication between the design and construction teams in the job site. In respect to the usage of 3D/4D modeling in the project studied, the difficulties to extract information from the 3D model has disable the usage of 4D modeling during construction phase. Therefore, the difficulties reported were identified as an opportunity to map deficiencies in the BIM model in order to define parameters for the new projects proposals and to automate the process of receiving the model and checking for inconsistencies or lack of information.